Anti-cancer effect of Annona Muricata Linn Leaves Crude Extract (AMCE) on breast cancer cell line. Issue 1 (December 2016) - Syed Najmuddin, Syed; Romli, Muhammad; Hamid, Muhajir; Alitheen, Noorjahan; Nik Abd Rahman, Nik
Abstract Background Annona muricata Linn which comes from Annonaceae family possesses many therapeutic benefits as reported in previous studies and to no surprise, it has been used in many cultures to treat various ailments including headaches, insomnia, and rheumatism to even treating cancer. However, Annona muricata Linn obtained from different cultivation area does not necessarily offer the same therapeutic effects towards breast cancer (in regards to its bioactive compound production). In this study, anti-proliferative and anti-cancer effects ofAnnona muricata crude extract (AMCE) on breast cancer cell lines were evaluated. Methods A screening of nineteen samples ofAnnona muricata from different location was determined by MTT assay on breast cancer cell lines (MCF-7, MDA-MB-231, and 4 T1) which revealed a varied potency (IC50 ) amongst them. Then, based on the IC50 profile from the anti-proliferative assay, further downward assays such as cell cycle analysis, Annexin V/FITC, AO/PI, migration, invasion, and wound healing assay were performed only with the most potent leaf aqueous extract (B1 AMCE) on 4 T1 breast cancer cell line to investigate its anti-cancer effect. Then, the in vivo anti-cancer study was conducted where mice were fed with extract after inducing the tumor. At the end of the experiment, histopathology of tumor section, tumor nitric oxide level, tumor malondialdehyde level, clonogenic assay, T cell immunophenotyping, and proteome profiler analysis were performed. Results Annona muricata crude extract samples exhibited different level of cytotoxicity toward breast cancer cell lines. The selected B1 AMCE reduced the tumor's size and weight, showed anti-metastatic features, and induced apoptosis in vitro and in vivo of the 4 T1 cells. Furthermore, it decreased the level of nitric oxide and malondialdehyde in tumor while also increased the level of white blood cell, T-cell, and natural killer cell population. Conclusion The results suggest that, B1 AMCE is a promising candidate for cancer treatment especially in breast cancer and deserves further research as an alternative to conventional drugs while also stressed out the selection of soursop sample which plays a significant role in determining its potential therapeutic effect on cancer.